THE ROLE OF STATE BUDGET REVENUES IN THE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Samandarova Gulmira Muzaffar qizi (European Science Publishing, 2025)
The article examines the role of state budget revenues in the socio-economic development of regions. Additionally, the analysis covers the share of state budget revenues in the gross domestic product (GDP) for the period 2020–2024, as well as the structure of state budget revenues during this period.
Keywords: State budget, budget planning, taxes, gross domestic product (GDP), local budget.